Unpredictable Nature of Nanofluid Flow: A Study on Effects of Uncertainties in Effective Viscosity. (2016) - Selvakumar, R. Deepak; Dhinakaran, S.
Abstract: A numerical analysis of steady, laminar and 2-D nanofluid flow around a circular cylinder has been carried out to showcase the effects of variable viscosity on flow characteristics. The governing equations of flow are solved using a finite-volume method based on SIMPLE algorithm. Three cases of simulations in which the effective viscosity of the nanofluid is calculated using (a) Classical Brinkman model, (b) Recent correlation from literature and (c) Experimental data from literature are performed. A comparative analysis of the three cases shows that the flow characteristics of nanofluids become unpredictable due to the uncertainties in effective viscosity. In the first case, nanofluids show an accelerated flow with earlier flow separation and longer wake bubbles. Whereas, in other two cases, a decelerated flow with delayed flow separation is noted. This is the first time; a decelerated flow of nanofluids has been reported in literature. It is understood that, flow characteristics of nanofluid vary both qualitatively and quantitatively due to the variations in effective viscosity. This work showcases the importance of precise effective viscosity models to clearly understand the flow features of nanofluids.